Method for producing substrate coated with intermediate layer and diamond layer

By coating the intermediate layer of aluminum oxide and AlCrXN on the cemented carbide and depositing the diamond layer in the CVD process, the problem of poor adhesion between the diamond layer and the cemented carbide substrate is solved, and the deposition of high-quality diamond layer and the wear resistance of the substrate is improved.

CN119836488APending Publication Date: 2025-04-15CARBONCOMPETENCE GMBH +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202280099752.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-09-05
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

When the diamond layer is applied to the cemented carbide, bonding negatively affects the nucleation and diamond growth, resulting in a decrease in the mass of the diamond layer and poor adhesion to the substrate.

Method used

The substrate surface is roughened by etching and a diamond layer is deposited on the nucleated surface of the intermediate layer in the CVD process using an intermediate layer containing aluminum oxide (Al2O3) and/or AlCrXN.

Benefits of technology

The intermediate layer significantly reduces the diffusion of atoms and/or ions in the substrate, improves the quality of the diamond layer and its adhesion to the substrate, and enhances the wear resistance and fracture resistance of the substrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836488A_ABST
    Figure CN119836488A_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a substrate coated with an intermediate layer and a diamond layer, comprising the steps of: (a) roughening a surface of the substrate with an etchant, (b) applying the intermediate layer on the roughened surface of the substrate, (c) nucleating the surface of the intermediate layer, and (d) coating a diamond layer on the nucleated surface of the intermediate layer by a chemical vapor deposition (CVD) process wherein the intermediate layer comprises alumina (Al2O3) and / or AlCrXN wherein Al is aluminum, Cr is chromium, X is a metalloid, preferably silicon (Si) or boron (B), and N is nitrogen. The invention also relates to a substrate having an intermediate layer and a diamond layer obtainable by said method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a substrate coated with an intermediate layer and a diamond layer, and a substrate coated with an intermediate layer and a diamond layer obtainable by said method. Background Art

[0002] Diamond coated tools have high hardness, good wear resistance, low friction coefficient, good thermal conductivity and low thermal expansion coefficient, thus having excellent cutting performance. The application of the diamond layer is usually carried out by chemical vapor deposition (CVD). However, it is difficult to apply the diamond layer directly to certain substrates, and the resulting diamond layer may not adhere well to the substrate. In particular, it is challenging to deposit the diamond layer on cemented carbide. Cemented carbide is a composite material including hard particles and a binding phase that binds the hard particles together, and the binding phase generally includes any one of cobalt, nickel and iron. When a diamond layer is applied to cemented carbide, the binding phase has a negative impact on nucleation and diamond growth, and promotes the formation of non-diamond carbon substances, which in turn reduces the quality of the diamond layer and its adhesion to the substrate.

[0003] Several methods are known in the art to improve the adhesion of the diamond layer to the substrate, in particular cemented carbide. Fundamentally, the bonding phase (cobalt in most cases) must be passivated. One method is to deplete the bonding phase from the near-surface area of ​​the cemented carbide by etching before applying the diamond layer. However, the removal of the bonding phase can lead to embrittlement and a reduction in fracture toughness, which is likely to cause fracture. According to another method, an intermediate layer having good adhesion to both the cemented carbide and the diamond layer can be deposited on the surface of the cemented carbide. The intermediate layer can act as a diffusion barrier for the bonding phase and can compensate for the thermal and / or mechanical stress differences between the substrate and the diamond layer.

[0004] DE4434428A1 discloses a composite material consisting of a main body based on hard metal, cermet, ceramic or steel, to which an intermediate layer and a polycrystalline diamond layer are applied. The intermediate layer comprises a predominantly tetrahedrally bonded amorphous carbon layer.

[0005] In EP2558610B1, a method for forming a coating including an intermediate layer and a diamond layer using PVD is disclosed. Si and C are Si x C 1-x-y-z N y M z The main component of the intermediate layer, M, is one or more elements selected from Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Y, B, Al and Ru (wherein 0.4≤x≤0.6, 0≤y≤0.1, and 0≤z≤0.2).

[0006] WO2018 / 112909A1 provides a method for pretreating cemented carbide before applying a diamond coating, wherein after etching the binder phase, the cemented carbide is coated with a coating comprising a bottom layer (diamond layer or cubic boron nitride layer), an intermediate layer and a top layer (tetrahedral amorphous carbon film layer). The intermediate layer comprises a metal transition layer and a core layer made of a metal nitride, a metal carbonate or a metal borate.

[0007] CN114134504A reports etching the tungsten carbide (WC) grains of cemented carbide tools with Murakami reagent and removing the binder phase with an acidic solution (e.g., a mixture of sulfuric acid and hydrogen peroxide), and then immersing the cemented carbide tool in a mixed solution of copper sulfate and chromium sulfate. The cobalt in the vicinity of the surface of the cemented carbide tool is partially replaced, and a cemented carbide tool having a cobalt subsurface layer covered by a copper-chromium layer is obtained. The treated cemented carbide tool can then be nucleated in a diamond powder suspension before starting CVD diamond growth.

[0008] US6214247B1 relates to a method for removing a portion of a binder phase from the surface of a substrate (e.g., cemented carbide, cermet or nitride) by etching gas to form voids in the surface. Subsequently, a coating comprising a material selected from the group consisting of TiC, TiN, TiCN, diamond, Al2O3, TiAlN, HfN, HfCN, HfC, ZrN, ZrC, ZrCN, Cr3C2, CrN and CrCN is deposited in these voids to increase the wear resistance of the substrate (e.g., metal cutting inserts, dies, punches).

[0009] US2003 / 129456A1 concerns a cemented carbide comprising a hard phase component comprising tungsten carbide and at least one material selected from carbides, nitrides and carbonitrides of metals of groups 4a, 5a and 6a of the periodic table. The cemented carbide may be coated with a layer comprising at least one of metal carbides, metal nitrides, metal carbonitrides, TiAlN, TiZrN, diamond-like carbon (DLC), diamond and Al2O3, wherein the metal is selected from groups 4a, 5a and 6a of the periodic table.

[0010] EP0503822A2 relates to a hard material (e.g. cemented carbide) onto which an intermediate layer is applied, for example, by CVD, PVD or sputtering. The intermediate layer consists of a material that can easily induce nucleation, for example a material containing silicon nitride, silicon carbide or Al2O3. The surface of the intermediate layer applied to the hard material is then roughened, for example by scratching or etching. This increases nucleation in a subsequent coating step to apply a diamond and / or diamond-like carbon coating.

[0011] US2013 / 164557A1 discloses a substrate coated with an intermediate layer in a PVD process. The intermediate layer has a metal portion consisting of more than 50 at% W and / or Cr. Before the PVD process, the substrate can be sandblasted (e.g., by sandblasting with hard material particles) to increase its roughness. After the PVD process, the applied intermediate layer can be roughened and pre-treated with abrasive and / or diamond particles for nucleation. The diamond layer is then applied by CVD. Summary of the invention

[0012] It is an object of the present invention to provide a substrate coated with an intermediate layer and a diamond layer, wherein the intermediate layer significantly reduces the diffusion of atoms and / or ions present in the substrate through the intermediate layer when the diamond layer is applied.

[0013] According to the claims, this object is solved by (i) a method for producing a substrate coated with an intermediate layer and a diamond layer, and (ii) a substrate coated with an intermediate layer and a diamond layer obtainable by said method.

[0014] The present invention relates to a method for preparing a substrate coated with an intermediate layer and a diamond layer, comprising the following steps:

[0015] (a) roughening the surface of the substrate using an etchant,

[0016] (b) coating an intermediate layer on the roughened surface of the substrate,

[0017] (c) nucleating a surface of the intermediate layer, and (e) coating a diamond layer on the nucleated surface of the intermediate layer by a chemical vapor deposition (CVD) process,

[0018] Wherein, the intermediate layer comprises aluminum oxide (Al2O3) and / or AlCrXN, wherein Al is aluminum, Cr is chromium, X is a metalloid, preferably silicon (Si) or boron (B), and N is nitrogen.

[0019] The substrate used in the present invention can be selected from metals, such as iron, molybdenum, tungsten and its alloys (such as tungsten carbide), hard alloys, steel (such as stainless steel, high-speed steel), silicon nitride or mixtures thereof. Various tools can be used as substrates, such as cutting tools (blades, handle tools), punching tools, knives, wear parts (such as molds or dies), etc. Therefore, it is further disclosed to use a substrate coated with an intermediate layer and a diamond layer as a tool.

[0020] The present invention has found that the use of an interlayer comprising Al2O3 and / or AlCrXN (particularly Al2O3, AlCrSiN, AlCrBN or mixtures thereof) provides an effective barrier to prevent atoms and / or ions present in the substrate (particularly the binder phase of cemented carbide) from diffusing through the interlayer during application of the diamond layer in a CVD process, which might otherwise negatively affect nucleation and diamond growth. This in turn might hinder the sp 3 The formation of hybrid carbon will, on the contrary, promote the formation of non-diamond carbon species, which will significantly reduce the quality of the diamond layer.

[0021] In a preferred embodiment according to the present invention, substrate is cemented carbide (also referred to as carbide). The intermediate layer provides an excellent diffusion barrier for the bonding phase present in the cemented carbide, otherwise the bonding phase may have an adverse effect on the diamond growth at the interface, thereby causing weak bonding. In the present invention, a high-quality diamond layer can be deposited on the intermediate layer, regardless of the grade of the cemented carbide as substrate. Particularly preferably, the cemented carbide comprising tungsten carbide as hard phase and cobalt as bonding phase is used as substrate in the present invention. Various amounts of cobalt, such as 3 to 12wt%, can be included in the cemented carbide substrate. First, tungsten carbide has high hardness, and secondly, it shows an excellent etching response (particularly when using Murakami reagent as etching agent), so that the surface of tungsten carbide can be well prepared for further processing.

[0022] Preferably, the intermediate layer consists of AlCrSiN, AlCrBN or Al2O3, which all have excellent high temperature stability in the diamond growth range up to 1,100°C. In addition, the surface energies of AlCrSiN, AlCrBN and Al2O3 allow for a high nucleation density when nucleation is performed, so that a closed diamond layer (i.e. a uniform layer, preferably without any holes or defects) can be deposited on the nucleation surface of the intermediate layer. In addition, AlCrSiN, AlCrBN and Al2O3 all show good adhesion to the substrate and provide excellent resistance to stresses, such as thermal stresses or mechanical stresses, which in turn facilitates the adhesion of the intermediate layer to the diamond layer. An intermediate layer comprising AlCrBN has the following advantages over an intermediate layer comprising AlCrSiN: not only is a good passivation of the binder phase obtained, but also internal stresses that could negatively affect adhesion can be minimized due to the similarity of the lattice of boron nitride (BN) to that of diamond.

[0023] Preferably, the Al2O3 used in the intermediate layer of the present invention is amorphous. The advantage of an amorphous Al2O3 layer is that it is more compact and dense than the crystalline structure of Al2O3, especially when deposited at low temperatures (e.g., below 300°C), so even very thin layers can be deposited in a closed manner and without pores.

[0024] According to the invention, the surface of the substrate is roughened with an etchant. A roughened surface is thereby obtained, which may allow deeper ingrowth of the intermediate layer, for example due to enhanced mechanical bonding. Furthermore, at least some of the binder phase present in the near-surface region of the substrate may be removed during the etching process, which increases the distance of the remaining binder phase from the subsequently applied diamond layer. This in turn reduces the diffusion of the binder phase (e.g. cobalt) during application of the diamond layer, thereby supporting the sp 3 The production of hybrid carbon, thereby improving adhesion. The substrate can be immersed in the etchant to ensure uniform etching of the entire surface. Before the etching step, the surface of the substrate can be mechanically pretreated (e.g., by wet sandblasting, dry sandblasting, drag finishing) and / or cleaned using a typical cleaning solution (e.g., with ultrasound) to remove unwanted substances, such as grinding lubricants, oils and residual contaminants, so as to prepare the surface for the subsequent etching step, which has nothing to do with the type of substrate used (e.g., when the substrate is cemented carbide, the carbide grade). Preferably, the surface of the substrate is cleaned before etching. The etchant is preferably applied in the form of an etching solution, i.e., a solution of the etchant in water, particularly a solution in demineralized water, and the concentration of the etchant is preferably in the range of 50 to 95 wt % (relative to the total weight of the solution). This allows a longer etching time to be applied without damaging the surface of the substrate, which in turn increases the roughness of the surface, thereby increasing the adhesion to the subsequently applied intermediate layer. Preferably, the surface of the substrate is etched at 20 to 40° C. for 30 seconds to 5 minutes. These conditions were found to prepare the substrate surface well for the subsequent coating step so that good adhesion to the interlayer could be achieved.

[0025] In a preferred embodiment of the present invention, the surface of the substrate is etched with Murakami reagent. Murakami reagent is an excellent etchant that can well roughen the surface of the substrate, thereby greatly enhancing the adhesion to the subsequently applied intermediate layer. Murakami reagent can include 1 part of potassium ferrocyanide III, 1 part of potassium hydroxide and 10 parts of water (by weight). Sodium hydroxide can also be used instead of potassium hydroxide. It is found in the present invention that Murakami reagent is particularly suitable for etching tungsten carbide (WC), thereby producing a surface with high roughness, which allows good mechanical bonding with the subsequently applied intermediate layer, thereby having good adhesion. Therefore, when tungsten carbide is included in the hard phase of the substrate, it is particularly preferred to use Murakami reagent as an etchant. Preferably, etching the surface of the substrate with Murakami reagent is carried out at a temperature in the range of 20 to 40°C for 30 seconds to 5 minutes. When these conditions are applied, the adhesion of the subsequently applied intermediate layer to the surface of the substrate can be significantly enhanced. In a particularly preferred embodiment, etching is carried out at 25°C for 3 minutes.

[0026] Further preferably, the etching of the present invention is carried out with a multi-step etching process. Therefore, according to a preferred embodiment of the present invention, acid etching is used after etching with Murakami reagent. Since Murakami reagent is alkaline, the components that cannot be etched and removed with Murakami reagent can be removed from the substrate with acid etching subsequently. The combined surface treatment of Murakami reagent and acid provides the best preparation of the substrate surface for the subsequent coating of the intermediate layer. On the one hand, the surface of the substrate can be significantly roughened, which improves the adhesion of the substrate to the intermediate layer through mechanical bonding. The resulting surface roughness makes it possible to obtain a flat and uniform intermediate layer when coating the surface of the substrate in a subsequent step. On the other hand, the bonding phase can be fully removed from the surface vicinity of the substrate, which causes the diffusion of the bonding phase to be significantly reduced during the application of the diamond layer by the CVD process.

[0027] When cemented carbide is used as a substrate in the present invention, the acid is preferably an acid that can serve as an etchant for the binder phase of the cemented carbide. In this way, at least some of the binder phase present in the surface of the cemented carbide (e.g., due to a previous grinding step) and in the area near the surface can be removed during etching. The consumption of the binder phase in the area near the surface can reduce the diffusion of the remaining binder phase in the deeper area of ​​the cemented carbide toward and through the subsequently applied intermediate layer, so that a high-quality diamond layer can be deposited. Between etching steps, the surface can be cleaned, for example, with water, preferably with demineralized water. Etching the substrate surface with acid is preferably performed at a temperature in the range of 20 to 40° C. for 30 seconds to 5 minutes. It was found that applying these conditions results in excellent adhesion of the subsequently applied intermediate layer to the surface of the substrate. Several acids are suitable for the present invention, such as nitric acid (or a solution thereof), sulfuric acid (or a solution thereof), or a persulfate solution (also known as caro acid). For example, several acids can be used in the subsequent etching step. The present invention preferably uses nitric acid because it is easy to handle and can be etched efficiently. In addition, nitric acid is particularly suitable for use in the case of cemented carbide as a substrate because it exhibits good etching efficiency for commonly used binder phases (especially cobalt). Particularly effective etching can be achieved when using aqueous nitric acid solution, wherein the concentration of nitric acid is 50 to 60 wt% (relative to the total weight of the solution).In a preferred embodiment, etching is performed with nitric acid (57 wt% solution) at 25°C for 60 seconds.

[0028] The present invention particularly preferably uses a two-step etching process to etch the surface of the substrate, etching with Murakami reagent and acid (preferably nitric acid). Preferably, the etching is carried out with Murakami reagent in the first step of the two-step etching process and with acid in the second step. It is particularly preferred to etch the surface of the substrate at a temperature of 20 to 40°C, wherein the etching is carried out with Murakami reagent for 30 seconds to 5 minutes and the etching is carried out with acid (especially nitric acid) for 30 seconds to 5 minutes. Preferably, an aqueous nitric acid solution with a nitric acid concentration of 50 to 60 wt% (relative to the total weight of the solution) is used. Following this etching scheme can excellently prepare the substrate for the coating step to apply the intermediate layer, so that good adhesion can be obtained. After the two-step etching process, the roughness value R of the etched surface of the substrate z It can be in the range of 0.1 μm to 2 μm. R can be calculated using the software of an optical microscope Keyence VHX-7000 (Keyence International, Belgium) by averaging the five highest peaks and five deepest valleys within a predetermined measurement length. z In addition, the average roughness R of the etched surface of the substrate a The range can be from 0.1 μm to 0.5 μm. In this application, the roughness values ​​were determined using an optical microscope Keyence VHX-7000 according to DIN EN ISO 4287 over a measuring length of 800 μm. It is worth noting that the exact roughness value depends on the roughness of the substrate surface obtained after grinding. When using tungsten carbide (WC) with a binder phase (especially cobalt) as the substrate, R z The value may be in the range of half the WC grain size (which may range from 0.2 μm to 5 μm, or even from below 0.2 μm to above 5 μm).

[0029] According to the present invention, a cleaning step of the substrate can be performed after the step of roughening the surface of the substrate with an etchant. Cleaning can be performed with water. This is used to remove the residues of the etchant and the residues of the etched substrate (for example, when cemented carbide is used as the substrate, the residues of the bonding phase). Preferably, the surface of the substrate is immersed in a water bath, for example, for up to 10 seconds or up to 20 seconds. After the immersion, it can be immersed in an ultrasonic bath filled with water for 1 to 5 minutes to produce a clean substrate surface without any residue. Preferably, demineralized water or deionized water is used to clean the surface of the substrate, so that any ionic contamination present in the water can be avoided. This ionic contamination may have a negative impact on the subsequent coating steps, in particular the adhesion of the substrate surface to the intermediate layer subsequently applied. For example, when the conductivity of an ultrasonic bath filled with demineralized water is measured to be reduced to less than 1 μS / cm using a water purity tester HI98309 (HannaInstruments, Graz, Austria), it can be considered that the cleaning is sufficient.

[0030] Subsequently, an intermediate layer is coated on the roughened surface of the substrate according to the present invention. The intermediate layer can be coated on the surface of the substrate by various thin film deposition processes (e.g., physical vapor deposition (PVD), chemical vapor deposition (CVD), atomic layer deposition (ALD) or sol-gel processes). Preferably, the surface of the substrate is coated by plasma enhanced atomic layer deposition (PE-ALD) or physical vapor deposition (PVD), because excellent results can be obtained in this way. For example, a uniform intermediate layer can be formed, which preferably does not have any holes or defects. The intermediate layer can include a single layer or multiple layers, such as two layers, three layers or more layers. The advantage of using a multilayer structure is that a material with high bonding strength to the substrate can be selected as an inner layer, and a material with high bonding strength to diamond can be selected as an outer layer. For example, the intermediate layer can include two layers, one of which contains Al2O3, and the other contains AlCrXN, preferably AlCrSiN or AlCrBN.

[0031] In the present invention, the average thickness of the intermediate layer is preferably in the range of 0.1 μm to 5 μm. If the average thickness is lower than 0.1 μm, the bonding strength will not be significantly improved and may even cause pinholes in the layer, while if the average thickness of the intermediate layer is higher than 5 μm, it will have a negative impact on the bonding strength and residual stress. The thickness values ​​of the layers (intermediate layer, diamond layer) given in this application are determined based on scanning electron microscope (SEM) images obtained from the cross-section of the substrate coated with these layers. The average thickness value is calculated based on three single measurements.

[0032] In a preferred embodiment according to the invention, an intermediate layer consisting of AlCrXN is applied on the roughened surface of the substrate by arc PVD. The arc PVD process can utilize standard direct current (DC) arc evaporation, with the arc controlled by an electromagnetic field or a permanent magnetic field setup. A multi-arc source setup can be used, for example by using two or three arcs. A bias voltage can be applied to the intermediate layer to generate an electric field, thereby controlling the energy of the ions so that they can reach the surface of the substrate to which the intermediate layer is to be applied. Al can be used. a Cr b X c The AlCrXN intermediate layer is formed by using a target material, wherein a is 50 to 80 at%, b is 20 to 50 at%, and c is 1 to 10 at%. The substrate temperature can be in the range of 400 to 500°C and can be maintained by one or more radiation heaters. The pressure during the coating process can be 5·10 -3 Until August 10 -2mbar range. The advantage of using an arc PVD process is that the intermediate layer can be irradiated with ions during the coating process by a conventionally applied substrate bias, thereby improving the compressive strength of the intermediate layer. After applying the arc PVD process, the surface of the intermediate layer formed can present droplets and increased roughness. Therefore, the surface of the intermediate layer can be smoothed by different surface finishing methods, such as wet or dry sandblasting, brushing, grinding or by drag and flow finishing processes. In a preferred embodiment according to the present invention, the intermediate layer can be smoothed by drag and flow finishing processes well known in the art. The coated substrate can be clamped in a rotating support and then immersed in a dry abrasive medium while rotating. The abrasive medium may include one or more abrasive particles, such as corundum particles, SiC particles, SiO2 particles, walnut shell particles, diamond particles, or a mixture of walnut shell particles and diamond particles. The particle diameter range of the abrasive medium can generally be 0.2 to 10 mm. This allows the reduction or even complete removal of droplets present on the surface of the intermediate layer formed during the arc PVD process, which can be excellently prepared for the subsequent steps of the method according to the present invention. The average thickness of the resulting intermediate layer ranged from 1 μm to 5 μm.

[0033] In another preferred embodiment according to the present invention, an intermediate layer consisting of Al2O3 is coated on the roughened surface of the substrate by PE-ALD. This is a self-limiting film growth method, which is characterized in that the growing film is alternately exposed to chemical precursors, thereby depositing (sub)monolayers in sequence. The main advantages of PE-ALD include high film density, low impurity content, good stoichiometry and excellent electronic properties. In addition, using PE-ALD, the chemical reactions during the Al2O3 deposition process can be started at lower temperatures in the range of 30 to 300°C. Therefore, the temperature window can be extended downward. Plasmas containing O2, N2, NH3, H2 or mixtures thereof can be used. Trimethylaluminum (TMA) and oxygen (O2) can be used as precursors for depositing Al2O3. Deposition can be carried out at 10 -1 The deposition process is carried out in a pressure range of 100 to 5 mbar. In contrast, under vacuum, the reaction of TMA and oxygen is too slow to allow deposition within an economical time. High-frequency pulsed oxygen plasma can be applied (radio frequency (RF) of 13.56 MHz, very high frequency (VHF) up to 60 MHz). It is sufficient to ignite the plasma only at the oxygen stage. Since oxygen does not react with TMA without excitation, time-consuming purging / evacuation is unnecessary. Instead, oxygen can be used directly as purge gas. The average thickness of the resulting Al2O3 interlayer ranges from 0.1 μm to 0.6 μm.

[0034] According to the invention, the surface of the intermediate layer is nucleated. The surface is the surface of the intermediate layer opposite to the surface facing the substrate. When the diamond layer is subsequently applied, nucleation of this surface of the intermediate layer supports the sp 3 Growth of hybrid carbon. Several nucleation processes can be used, such as (a) scratching the substrate, for example manually using diamond paste or industrially by sandblasting; (b) ultrasonic seeding by a mixture of solvent (e.g. isopropyl alcohol or demineralized water) and hard material particles (e.g. diamond particles or particles of Al2O3, SiC, BC, etc.); (c) bias enhanced nucleation (BEN), whereby a negative potential is applied to accelerate the charged species and bring them to the substrate surface; (d) electrospraying; or (e) dip coating.

[0035] It is particularly preferred in the present invention that a nucleation surface of the intermediate layer is higher than 10 10 / cm2 high nucleation density. The density can be determined by counting the seeds in the image obtained from the scanning electron microscope (SEM) using image processing software. This allows the subsequently applied diamond layer to have low roughness and excellent uniformity (e.g., significantly reduced or even no holes and inhomogeneities). In addition, due to good adhesion, a closed diamond layer can be formed at an early stage of growth. For example, such a high nucleation density can be obtained by the following process: a colloid of diamond particles with a determined grain size (e.g., 5nm to 10nm) can be dissolved in a solvent. The use of isopropanol or demineralized water as a solvent has been shown to achieve good nucleation efficiency. The substrate coated with the intermediate layer can be nucleated in an ultrasonic bath for 10 minutes to several hours, depending on the concentration of the diamond particles (0.1 to 10ct / liter) and the power of the ultrasonic device (100 to 1,000W). Preferably, the nucleation time in the ultrasonic bath is 10 to 30 minutes. Further preferably, the temperature in the ultrasonic bath can be in the range of 0°C to 20°C. Effective nucleation can be achieved using any of these parameters.

[0036] According to the present invention, a diamond layer is subsequently coated onto the nucleation surface of the intermediate layer by a CVD process. The diamond layer according to the present invention is intended to refer to a microcrystalline or nanocrystalline diamond layer, or a combination of the two (e.g. as a multilayer or gradient layer). A hot wire (HF-) CVD process known in the art can be used. Alternatively, the apparatus and method disclosed in WO2018 / 064694A1 can be used to perform the CVD process of the present invention. The substrate including the intermediate layer can then be placed in a deposition chamber as a substrate. A process gas (hydrogen or a mixture of hydrogen and a carbon-containing gas, such as methane) can be supplied to the flow channel of the gas activation element through a gas inlet. The wall surrounding the flow channel of the gas activation element can be heated, preferably at a temperature of at least 2,000°C, so that the process gas in the flow channel can be thermally excited. The cross-sectional area of ​​the flow channel is preferably between 5 and 30 mm 2range to increase the impact excitation of the process gas with the wall. Further preferably, the flow channel of the gas activation element is closed at both ends, for example, with a closing body, so that the gas activation element has no openings except for the inlet opening and the outlet opening. The ratio between the area of ​​exactly one outlet opening and the cross-sectional area of ​​the gas activation element is preferably 1:5 to 1:20, in particular 1:10, which further increases the excitation rate of the process gas. Due to the small number of openings and the closure of the flow channel at both ends, the partial pressure in the flow channel inside the gas activation element can be significantly increased. Therefore, the partial pressure can be several times higher than the pressure in the separation chamber. This allows the process gas to be further excited by impact excitation (such as collision induced dissociation) as well as thermal excitation. Therefore, preferably, the process gas containing hydrogen is excited by a combination of thermal excitation and impact excitation. This produces an atomic hydrogen excitation rate of 80% and above, while thermal excitation alone can only result in an excitation rate of up to 30%. Such a high excitation rate can accelerate the diamond growth rate and produce a diamond layer with a high purity. In addition, due to the high excitation rate of the present invention and the controlled flow of the process gas, the distance between the gas activation element and the substrate can be increased, which significantly improves the uniformity of the deposited diamond layer. In the known hot wire CVD process, due to the low excitation rate of the process gas introduced into the chamber in the background, it is necessary to select a small distance between the gas activation element and the substrate (usually in the range of 5 to 10 mm) without local control. In contrast, in the CVD process according to WO2018 / 064694A1, due to the relatively high excitation rate of the process gas, a larger distance can be set between the gas activation element and the substrate surface. The distance is preferably in the range of 20 to 100 mm, particularly preferably in the range of 40 to 60 mm, which ensures a uniform temperature distribution on the substrate surface, thereby improving the uniformity of the deposited diamond layer. During the deposition of the diamond layer on the surface of the substrate, the temperature range of the substrate may be 750°C to 950°C. In the present invention, the substrate temperature is preferably in the range of 750°C to 850°C. The duration of the CVD process depends on the target thickness, typically in the range of 10 hours to 20 hours. Additionally, the pressure in the deposition chamber may range from 1 to 40 mbar. Using any of these parameters will help produce a uniform diamond layer.

[0037] By means of the method according to the invention, intermediate layers and diamond layers which are almost or even completely free of pinholes can be produced, so that good interlayer adhesion and good adhesion to the substrate surface can be achieved. Furthermore, during the application of the diamond layer, the diffusion of atoms from the substrate (e.g. from its binder phase) into the diamond layer can be reduced or even avoided. In the present invention, the formation of a layer which is almost free of pinholes or free of pinholes can be ensured by careful selection of the processing parameters and an optional cleaning step to avoid the presence of dust, contaminants or inclusions in the layer formed.

[0038] The invention also relates to a substrate coated with an intermediate layer and a diamond layer obtainable by the method of the invention. The intermediate layer is arranged between the substrate and the diamond layer.

[0039] According to a preferred embodiment of the present invention, the intermediate layer has an average thickness in the range of 1 μm to 5 μm, preferably 2 μm to 4 μm, and is composed of AlCrSiN or AlCrBN. Therefore, the intermediate layer can be almost or even completely pinhole-free, can well compensate for the difference in thermal stress and / or mechanical stress between the substrate and the diamond layer, and has excellent adhesion to both the substrate and the diamond layer. In addition, if the substrate is a cemented carbide, the intermediate layer can provide an excellent diffusion barrier for the bonding phase of the cemented carbide.

[0040] In an alternative preferred embodiment, the intermediate layer has an average thickness in the range of 0.1 μm to 0.6 μm, preferably 0.1 μm to 0.2 μm, and is composed of aluminum oxide (Al2O3). Thus, the intermediate layer can be almost or even completely pinhole-free, can well compensate for differences in thermal and / or mechanical stresses between the substrate and the diamond layer, and has excellent adhesion to both the substrate and the diamond layer. In addition, if the substrate is a cemented carbide, the intermediate layer can provide an excellent diffusion barrier for the cemented carbide's binder phase.

[0041] Preferably, the diamond layer according to the present invention comprises at least 95 wt% sp 3 Hybridized carbon (ie diamond), more preferably at least 98 wt% sp 3 Hybridized carbon, particularly preferably at least 99 wt % sp 3 Hybridized carbon. This ensures good quality of the diamond layer and excellent adhesion to the intermediate layer. The average thickness of the diamond layer is preferably in the range of 0.1 μm to 300 μm. An average thickness below 0.1 μm is insufficient to provide a significant improvement in performance (e.g. wear resistance), while an average thickness above 300 μm does not produce a further significant improvement in performance.

[0042] Due to the diamond layer, the coated substrate according to the present invention exhibits high hardness and high wear resistance. Therefore, excellent wear resistance and fracture resistance as well as good adhesion and toughness can be achieved, thereby improving durability.

[0043] Preferably, in the present invention, the area fraction of the substrate binder phase present in the intermediate layer is less than 15%, more preferably less than 12%, and most preferably less than 8%, relative to the total area of ​​the intermediate layer, as determined from a cross section of the coated substrate by energy dispersive X-ray spectroscopy (EDX) analysis. Preferably, the substrate is a cemented carbide and the binder phase comprises cobalt or even consists of cobalt. The area fraction can be determined by subjecting the substrate coated with the intermediate layer to a heat treatment at 900° C. for 10 hours under an argon atmosphere (i.e. the conditions usually applied during a CVD process), followed by preparing a cross section of the coated substrate and generating an EDX image. It is worth noting that the preferred temperature range during the CVD process according to the present invention is 750 to 850° C., however, the use of higher temperatures during the heat treatment can facilitate the evaluation of the diffusion properties of the intermediate layer. When the coated substrate is subjected to said heat treatment, no diamond layer is applied before the EDX analysis. However, the area fraction can also be determined from a cross section of the substrate coated with the intermediate layer and the diamond layer, in which case the heat treatment as described above is replaced by a CVD process. The results obtained when the CVD process was carried out at a temperature of 850° C. for 10 hours correspond to the results obtained when a substrate coated with an intermediate layer (and without a diamond layer) was heat treated. Due to the low diffusivity, the intermediate layer according to the invention can act as an excellent diffusion barrier, which significantly reduces or even completely prevents the diffusion of the binder phase in the cemented carbide to the intermediate layer and through the intermediate layer. The adhesion of the diamond layer to the intermediate layer can therefore be significantly improved. Therefore, a high-quality diamond layer can be deposited. It was found that the use of an intermediate layer composed of AlCrSiN, AlCrBN or Al2O3 can obtain a particularly low diffusion of the binder phase (in particular cobalt). In contrast, when an intermediate layer different from the present invention is used, the area fraction of the binder phase present in the intermediate layer can be significantly higher, for example higher than 15% or even higher than 20% relative to the total area of ​​the intermediate layer. This in turn reduces the adhesion and thus affects the quality of the diamond layer.

[0044] According to the present invention, preferably, the roughness of the nucleation surface of the intermediate layer is in the same range as the surface of the etched substrate. Preferably, the roughness R of the nucleation surface of the intermediate layer is z The range is from 0.1 μm to 2 μm, particularly preferably from 0.2 μm to 2 μm, as determined in accordance with DIN EN ISO 4287 using an optical microscope Keyence VHX-7000.

[0045] When tungsten carbide (WC) with a binder phase (particularly cobalt) is used as the substrate, preferably the roughness of the cemented carbide is in the range of half the grain size of WC (its grain size may range from 0.2 μm to 5 μm, or even from less than 0.2 μm to more than 5 μm). When an intermediate layer consisting of Al2O3 is applied, its surface may exhibit a roughness similar to that of the surface of the etched substrate, since the average thickness of the Al2O3 layer is small (e.g., below 0.2 μm). On the contrary, when an intermediate layer consisting of AlCrSiN or AlCrBN is applied, a lower roughness is obtained compared to the surface of the underlying substrate, since the average thickness of the AlCrSiN or AlCrBN layer is relatively high (e.g., 2 μm to 4 μm). BRIEF DESCRIPTION OF THE DRAWINGS

[0046] The present invention will be further explained below with reference to examples and accompanying drawings.

[0047] Figure 1a -b shows a SEM image (taken using Tescan Mira, Tesca GmbH, Germany) of the ground surface of the cemented carbide substrate (magnification: 10,000). Figure 1a Display secondary electron (SE) images, Figure 1b A backscattered electron (BSE) image is shown. It can be seen that after grinding (i.e. before etching), the cobalt binder phase of the substrate is smoothed on the surface.

[0048] Figure 2a -b and Figure 3a -b shows Figure 1a -b is an SEM image (taken using a Tescan Mira) of the surface of the cemented carbide substrate after roughening using a two-step etching process (using Murakami's reagent and nitric acid). Figure 2a and Figure 3a Display SE image, while Figure 2b and Figure 3b Display the BSE image. Figure 2a -b has a magnification of 10,000, Figure 3a - Magnification in b is 20,000.

[0049] Figure 4 SEM images (taken using Hitachi SU-8010, Hitachi High-Technologies Corp., Japan) of fracture edges of substrates comprising tungsten carbide as hard phase and cobalt as binder phase, and coated with an Al2O3 layer (average thickness 0.2 μm) are shown.

[0050] Figure 5Shown is an SEM image (taken using a Hitachi SU-8010) of a fracture edge of a substrate comprising tungsten carbide as a hard phase and cobalt as a binder phase, and coated with an AlCrSiN layer (average thickness 4 μm) and a diamond layer (average thickness 6 μm).

[0051] Figure 6a -b shows the use of a composite material comprising tungsten carbide as a hard phase and cobalt as a binder phase, and coated with an intermediate layer ( Figure 6a Al2O3 and Figure 6b Scratch test results of AlCrSiN) and diamond layer substrates.

[0052] Figure 7a -b shows an EDX image of a cross section of a substrate coated with a reference interlayer, showing significant diffusion of cobalt through the interlayer after the coated substrate was heat treated at 900°C for 10 hours in an argon atmosphere in a vacuum furnace (DSVF-3, Daeheung Science Co., Korea). Figure 7a In the example, aC:H:Si (average thickness of 2 μm) was used as the intermediate layer, while in Figure 7b In the present invention, aC:H:N (average thickness of 1.5 μm) was applied.

[0053] Figure 8 An EDX image of a cross section of a substrate coated with an AlCrSiN intermediate layer (average thickness 4 μm) according to the present invention is shown, showing relatively low cobalt diffusion after heat treatment of the coated substrate at 900°C for 10 hours in an argon atmosphere in a vacuum furnace (DSVF-3, Daxing Scientific Corporation). DETAILED DESCRIPTION

[0054] Example

[0055] Example 1 - Preparation of a substrate coated with an intermediate layer and a diamond layer according to the present invention

[0056] Substrates with a diameter of 6 mm and a length of 50 mm, comprising tungsten carbide (WC) as a hard phase and cobalt as a binder phase (WC grain size of 0.7 μm to 1.2 μm, Co content of 6 wt% to 10 wt%), were cleaned by a standard cleaning process to remove lubricant and oil residues. The surface of the substrate was roughened by a two-step etching process using Murakami reagent and then nitric acid (53 wt%) in an ultrasonic bath until the average R obtained after etching was 0.1 %. zThe maximum value is half the size of the WC grain. The surface of the substrate was etched with Murakami reagent at 25°C for 180 seconds and with nitric acid at 25°C for 60 seconds. Subsequently, the surface roughness distribution of the substrate within a length range of 800 μm was measured using a Keyence VHX-7000 optical microscope according to DIN EN ISO 4287. Based on the obtained roughness distribution, the final roughness value R was calculated using Keyence software. z and R a , 0.98 μm and 0.14 μm, respectively. Subsequently, amorphous Al2O3 and AlCrSiN were coated on the etched surface of the substrate as intermediate layers, respectively.

[0057] (A) Amorphous Al2O3 as an intermediate layer

[0058] An amorphous aluminum oxide (Al2O3) layer was deposited on the surface of the roughened substrate by PE-ALD over a coating length of 30 mm. An Al2O3 layer with an average thickness of 0.2 μm was obtained, covering the entire surface area of ​​the substrate. The well-established PE-ALD process was employed using two precursors, trimethylaluminum (TMA) and oxygen (O2), in a pressure range of 10 -1 The process is carried out under a pre-vacuum of up to 5 mbar. At a process temperature below 100°C, the oxygen plasma is ignited by high frequency (13.56 MHz). Figure 4 SEM images of the fractured edges of substrates coated with an Al2O3 layer are shown.

[0059] The surface of the Al2O3 layer was then nucleated in an ultrasonic bath filled with diamond suspension (0.25 g suspended in 900 ml of isopropanol) at 0°C and 300 W for 10 minutes. Subsequently, a nanocrystalline diamond layer with an average thickness of 6 μm was coated on the nucleation surface of the Al2O3 layer in a CVD process using process gases of hydrogen 5.0 and methane 3.5, using the apparatus described in WO2018 / 064694A1. The process was carried out at a temperature in the range of 800°C to 850°C and a pressure of 10 mbar.

[0060] (B) AlCrSiN as an intermediate layer

[0061] At a temperature of 400°C to 500°C and 5·10 -3 mbar to 8.10 -2 The AlCrSiN layer was deposited on the surface of the roughened substrate by arc PVD at a pressure of mbar over a coating length of 35 mm. a Cr b X cThe target material, where a is 60at%, b is 30at%, and c is 10at%. The average thickness of the obtained AlCrSiN layer is 4μm, uniformly covering the entire surface of the substrate. The surface of the obtained intermediate layer is then smoothed by a drag and flow finishing process.

[0062] Subsequently, the surface of the AlCrSiN layer was nucleated at 0°C and 300W for 10 minutes in an ultrasonic bath filled with a diamond suspension (0.25 g dissolved in 900 ml of isopropanol). Subsequently, a nanocrystalline diamond layer with an average grain size of 5 to 15 nm and an average thickness of 6 μm was coated on the nucleation surface of the AlCrSiN layer in a CVD process using process gases hydrogen 5.0 and methane 3.5 using the apparatus described in WO2018 / 064694A1. The process was carried out in a temperature range of 800°C to 850°C and a pressure of 10 mbar. Figure 5 SEM images of fractured edges of substrates coated with an AlCrSiN layer and a diamond layer are shown.

[0063] Example 2 – Adhesion Test

[0064] Adhesion tests were performed on substrates coated with an interlayer (Al2O3 or AlCrSiN) and a diamond layer as prepared in Example 1 by dry blasting with corundum particles (F90, 125 to 180 μm) at 3 bar. Both interlayers showed good adhesion to the substrate for up to 30 seconds for AlCrSiN and more than 120 seconds for Al2O3 without any interlayer peeling or damage occurring.

[0065] Example 3 – Scratch Test

[0066] The substrate coated with the intermediate layer (Al2O3 or AlCrSiN) and the diamond layer as prepared in Example 1 was further subjected to a scratch test. The scratch test was performed using an automatic scratch tester that complies with ASTM C1624, ISO 20502 and ISO EN 1071. Scratch Tester RST 3 (Anton Paar, Austria). This scratch tester is widely used to characterize hard coating materials with typical coating thickness exceeding 1 μm. The following parameters were used: diamond Rockwell indenter with a radius of 200 μm, progressive load scratch mode, scratch length 2 mm, scratch load 0.5 to 60 N, load rate 300 N / min. The critical load (Lc) for substrates coated with Al2O3 as an intermediate layer was 66 N (see Figure 6a ), the critical load (Lc) of the substrate coated with AlCrSiN as the intermediate layer is 73N (see Figure 6b ).

[0067] Example 4 – Diffusion of Cobalt through an Interlayer

[0068] The diffusion of cobalt present as a bonding phase in the tungsten carbide substrate through various intermediate layers was analyzed by energy dispersive X-ray spectroscopy (EDX) analysis. Each substrate coated with a different intermediate layer was heat treated at 900°C for 10 hours in a vacuum furnace (DSVF-3, Daxing Science Co., Ltd.) under an argon atmosphere. After the heat treatment, a cross section of the coated substrate was prepared for EDX analysis, which was performed using a field emission scanning electron microscope Hitachi SU8010 and an EDX device Horiba X-MaxN50 (Horiba Ltd., Japan). The cross section of the coated substrate was loaded into a vacuum chamber through a subchamber. The measurement was performed at room temperature (20 to 25°C) and the vacuum chamber pressure was 10 -4 Up to 10 -3 The voltage and current were 10 kV and 10 μA, respectively, in the Pa range. Images were taken at 300,000 counts / image, a processing time of 4 seconds, a pixel dwell time of 10 milliseconds, and 1024 channels. The EDX unit was operated cold, and a working distance of 15 mm was applied.

[0069] Substrates coated with intermediate layers were prepared according to the preparation method disclosed in Example 1. The following systems are examples of various tested intermediate layers (average thickness and coating method in parentheses): SiO2 (1 μm; PE-CVD), aC:H:Si (2 μm; PE-CVD), aC:H:N (1.5 μm; PE-CVD), AlTiN (1 μm, 2 μm; arc PVD), AlTiSiN (1 μm, 2 μm; arc PVD), AlCrN (1 μm, 2 μm; arc PVD), AlCrSiN, using various targets with Si content ranging from 1 to 10 at% (1 μm, 2 μm, 4 μm; arc PVD), Al2O3 (0.2 μm; PE-ALD); Cr (1 μm; arc PVD) and Ti (1 μm; arc PVD).

[0070] EDX analysis confirmed that cobalt diffused significantly from the substrate into and through most of the analyzed interlayers, toward the surface of the interlayer opposite to its surface facing the substrate. The area fraction of cobalt present in the interlayer after heat treatment was calculated from the cross-sectional EDX images using conventional image processing software. Figure 7a and Figure 7bExemplary EDX images of cross sections of substrates coated with an aC:H:Si interlayer (average thickness 2 μm) and coated with an aC:H:N interlayer (average thickness 1.5 μm) are shown, respectively. The area fraction of cobalt present in the interlayer after heat treatment is 19% for the substrate coated with aC:H:Si and 23% for the substrate coated with aC:H:N (both relative to the total area of ​​the interlayer). In contrast, when the substrate is coated with an inventive interlayer consisting of AlCrSiN or Al2O3, respectively, EDX analysis surprisingly shows a significant reduction in the diffusion of cobalt into and through these two interlayers. Figure 8 An exemplary EDX image of a cross section of a substrate coated with an AlCrSiN interlayer (average thickness 4 μm) is shown. The area fraction of cobalt present in the AlCrSiN layer after heat treatment is only 6% (relative to the total area of ​​the interlayer), which confirms the excellent ability of the interlayer of the present invention to act as a cobalt passivation layer. Example 5 - Performance testing of cemented carbide tools coated with interlayers and diamond layers

[0071] A cemented carbide milling cutter having a diameter of 10 mm, comprising tungsten carbide (WC) as cemented carbide (WC grain size of 1 μm) and cobalt (Co) as a binder phase (Co content of 6 wt%), was coated with an intermediate layer and a nanocrystalline diamond layer (average thickness of 6 μm) according to the preparation method of Example 1. An Al2O3 layer (average thickness of 0.2 μm) was applied by PE-ALD, while an AlCrSiN layer (average thickness of 4 μm) was applied by arc PVD. In addition, the cemented carbide milling cutter was wet etched to remove cobalt and then coated with a diamond layer as a reference (i.e., not coated with an intermediate layer). For all prepared cemented carbide milling cutters, the average thickness of the nanocrystalline diamond layer was 6 μm. Wear was measured using average wear width markings after 36 m milling path processing of a highly abrasive carbon fiber reinforced polymer (CFRP; T700 type carbon fiber, tow size of 12 k).

[0072] The results show that the performance is significantly better when using a cemented carbide milling cutter coated with an intermediate layer and a diamond layer according to the invention. That is, when Al2O3 and AlCrSiN were used as intermediate layers, the average wear was only 118 μm and 65 μm, respectively. In contrast, when the substrate was wet-etched and the diamond layer was subsequently applied, the average wear was significantly higher, at 174 μm.

Claims

1. A method for preparing a substrate coated with an intermediate layer and a diamond layer, comprising the following steps: (a) roughening the surface of the substrate using an etchant, (b) coating an intermediate layer on the roughened surface of the substrate, (c) nucleating the surface of the intermediate layer, and (d) coating a diamond layer on the nucleated surface of the intermediate layer by a chemical vapor deposition (CVD) process, Wherein, the intermediate layer comprises aluminum oxide (Al2O3) and / or AlCrXN, wherein Al is aluminum, Cr is chromium, X is a metalloid, preferably silicon (Si) or boron (B), and N is nitrogen.

2. The method according to claim 1, characterized in that The substrate is cemented carbide.

3. The method according to claim 1 or 2, characterized in that: The intermediate layer is composed of AlCrSiN, AlCrBN or Al2O3.

4. The method according to any one of claims 1 to 3, characterized in that Al2O3 is amorphous.

5. The method according to any one of claims 1 to 4, characterized in that The surface of the substrate is etched using Murakami's reagent.

6. The method according to claim 5, characterized in that The surface of the substrate is etched by a two-step etching process using Murakami's reagent and an acid, preferably nitric acid.

7. The method according to claim 6, characterized in that The surface of the substrate is etched at a temperature of 20° C. to 40° C., wherein the Murakami reagent is used for etching for 30 seconds to 5 minutes, and the nitric acid is used for etching for 30 seconds to 5 minutes.

8. The method according to any one of claims 1 to 7, characterized in that An intermediate layer consisting of AlCrXN is applied on the surface of the substrate by arc physical vapor deposition (PVD).

9. The method according to any one of claims 1 to 7, characterized in that An intermediate layer composed of Al2O3 is coated on the surface of the substrate by plasma enhanced atomic layer deposition (PE-ALD).

10. The method according to any one of claims 1 to 9, characterized in that In the CVD process, a process gas containing hydrogen is activated by a combination of thermal activation and shock excitation.

11. A substrate coated with an intermediate layer and a diamond layer obtainable by a method according to any one of claims 1 to 10.

12. The substrate according to claim 11, characterized in that The intermediate layer has an average thickness in a range of 1 μm to 5 μm, and the intermediate layer consists of AlCrSiN or AlCrBN.

13. The substrate according to claim 11, characterized in that The intermediate layer has an average thickness in a range of 0.1 μm to 0.6 μm, and the intermediate layer is composed of aluminum oxide (Al 2 O 3 ).

14. The substrate according to any one of claims 11 to 13, characterized in that The area fraction of the binder phase of the substrate present in the interlayer is lower than 15% relative to the total area of ​​the interlayer, as determined from a cross section of the coated substrate by energy dispersive X-ray spectroscopy (EDX) analysis according to the specification.

15. The substrate according to any one of claims 11 to 14, characterized in that The nucleation surface of the intermediate layer has a roughness R in the range of 0.1 μm to 2 μm. z , as determined according to the instructions.

Citation Information

Patent Citations

  • composite body, use of this composite body and method for its production

    DE4434428A1

  • A diamond- and / or diamond-like carbon-coated hard material

    EP0503822A2

  • Hard carbon coating and method of forming the same

    EP2558610B1

  • Cemented carbide and cutting tool

    US20030129456A1

  • Coated body and a process for coating a body

    US20130164557A1